1999
DOI: 10.1046/j.1471-4159.1999.0730859.x
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐Dihydroxyvitamin D3 Regulates the Synthesis of γ‐Glutamyl Transpeptidase and Glutathione Levels in Rat Primary Astrocytes

Abstract: Astrocytes play a pivotal role in CNS detoxification pathways, where glutathione (GSH) is involved in the elimination of oxygen and nitrogen reactive species such as nitric oxide. We have previously demonstrated that the specific activity of ␥-glutamyl transpeptidase (␥-GT), an enzyme of central significance in GSH metabolism, is regulated in vivo in astrocytes by 1,25-dihydroxyvitamin D 3 (1,25-D 3 ). The aim of the present work was to investigate, in primary cultures of newborn rat astrocytes, the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(150 citation statements)
references
References 68 publications
(72 reference statements)
3
143
0
4
Order By: Relevance
“…41 1,25-VD enhanced intracellular GSH pools, and thus decreased free radical formation in rat primary astrocytes. 42 Furthermore, vitamin D has also been reported to reduce oxidative stress by upregulating antioxidant systems, including GSH, GPx and superoxide dismutase in rats. 43 The results from these studies suggested that vitamin D participated in antioxidant machinery and protected cells from oxidative challenge.…”
Section: Discussionmentioning
confidence: 99%
“…41 1,25-VD enhanced intracellular GSH pools, and thus decreased free radical formation in rat primary astrocytes. 42 Furthermore, vitamin D has also been reported to reduce oxidative stress by upregulating antioxidant systems, including GSH, GPx and superoxide dismutase in rats. 43 The results from these studies suggested that vitamin D participated in antioxidant machinery and protected cells from oxidative challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D might show its neuroprotective effect also by controlling brain detoxification processes (Wiseman 1993;Garcion et al 1997Garcion et al , 1999Wang et al 2001;Garcion et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…During transient ischemic events, transforming growth factor and GDNF are upregulated in hippocampal cells to promote survival (Garcion, Sindji et al 1999). As discussed earlier, vitamin D augments innate antioxidative defenses by increasing glutathione and GDNF concentrations (Wion, MacGrogan et al 1991;Naveilhan, Neveu et al 1996).…”
Section: Vitamin D Cerebrovascular Disease and Vascular Dementiamentioning
confidence: 92%